2013
DOI: 10.1007/s00422-012-0538-y
|View full text |Cite
|
Sign up to set email alerts
|

From lamprey to salamander: an exploratory modeling study on the architecture of the spinal locomotor networks in the salamander

Abstract: The evolutionary transition from water to land required new locomotor modes and corresponding adjustments of the spinal "central pattern generators" for locomotion. Salamanders resemble the first terrestrial tetrapods and represent a key animal for the study of these changes. Based on recent physiological data from salamanders, and previous work on the swimming, limbless lamprey, we present a model of the basic oscillatory network in the salamander spinal cord, the spinal segment. Model neurons are of the Hodg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 148 publications
(240 reference statements)
1
29
0
Order By: Relevance
“…These other treatment conditions may include modulation or removal of subsets of currents that elicit characteristic oscillatory behaviors such as seizure-like activities or slow subthreshold oscillations (Grillner et al, 1995; Cymbalyuk and Calabrese, 2000, 2001; Krishnan and Bazhenov, 2011; Jasinski et al, 2013; Barnett et al, 2013; Bicanski et al, 2013; Doloc-Mihu and Calabrese, 2014; Krishnan et al, 2015). Moreover, the greater sensitivity of the model without h -current to the monensin rate constant suggests that the h -current plays a protective role to prevent disruption of functional activity in oscillator heart interneurons, consistent with previous observations (Cymbalyuk et al, 2002; Marin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These other treatment conditions may include modulation or removal of subsets of currents that elicit characteristic oscillatory behaviors such as seizure-like activities or slow subthreshold oscillations (Grillner et al, 1995; Cymbalyuk and Calabrese, 2000, 2001; Krishnan and Bazhenov, 2011; Jasinski et al, 2013; Barnett et al, 2013; Bicanski et al, 2013; Doloc-Mihu and Calabrese, 2014; Krishnan et al, 2015). Moreover, the greater sensitivity of the model without h -current to the monensin rate constant suggests that the h -current plays a protective role to prevent disruption of functional activity in oscillator heart interneurons, consistent with previous observations (Cymbalyuk et al, 2002; Marin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The anatomy of the RS system was described in this animal by tracing studies (Naujoks‐Manteuffel and Manteuffel, ; Sanchez‐Camacho et al, ; Hubbard et al, ) and some RS cells were shown to be glutamatergic (Chevallier et al, ). The key role of RS cells in controlling the spinal locomotor CPG was recently modeled (Bicanski et al, ). The salamander MLR controls locomotor output (Cabelguen et al, ), and we now show that the strength of MLR stimulation controls the Ca 2+ responses of RS neurons of the rostral and caudal hindbrain.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these new findings, we have recently proposed a tentative model of axial spinal segments and hemisegments of the salamander spinal cord at the cellular level, using a biophysical model adapted from the lamprey literature (Bicanski et al 2011(Bicanski et al , 2012, in the same issue). The neuron model was a simplified version of the multicompartment Hodgkin-Huxley model used by Wallén et al (1992) (reduced from 5 to 3 compartments).…”
Section: The Trunk Networkmentioning
confidence: 99%
“…Both E and C populations have axons extending longer in the caudal direction. C Segmental network in Bicanski et al (2012).…”
Section: The Tail Networkmentioning
confidence: 99%